Fabrication of PW11Zn@MOF-808 and its catalytic activity for oxidative desulfurization of fuel oil: Kinetics, thermodynamics and mechanism - Haruna, Abdurrashid; Aljunid Merican, Zulkifli Merican; Abdul Rahman, Mohd Basyaruddin; Musa, Suleiman Gani; Al-Yaari, Abdullah (Elsevier, 2023)
At present, metal-organic frameworks (MOFs) supported with Keggin-type polyoxometalates (POMs) have been proven to be an effective approach for the development of high-performing heterogeneous catalysts. Herein, a Keggin-type PW11Zn was encapsulated within MOF-808 (PW11Zn@MOF-808) through an environmentally friendly one-pot solvothermal approach. Several analytical techniques such as FTIR, XRD, BET, FE-SEM, and XPS were employed for the material's characterization. The newly developed catalysts demonstrated the synergistic properties of the pristine components and their catalytic activity has been tested for the oxidative desulfurization of dibenzothiophene (DBT) in liquid fuel oil. PW11Zn@MOF-808 behaved as excellent catalyst and indicated a DBT conversion of 99.4% which is 1.145 times higher than MOF-808 with a DBT removal capacity of 86.85%. The reaction was optimized at ambient conditions of 50 °C, 30.0 mg of catalyst dose, and oxidant-to-sulfur (O/S) molar ratio of 5. The catalyst showed good reusability with no obvious loss in its initial activity after recycling for eight times. Also, the kinetics and thermodynamic analysis of the oxidation reaction was studied.